DETERMINANTS OF BLOCKCHAIN TECHNOLOGY ADOPTION INTENTION IN PUBLIC FINANCIAL MANAGEMENT OF KUTAI KARTANEGARA REGENCY - Muhammad Adib; Rifqi Muhammad (JAT : Journal Of Accounting and Tax, 2026)
Public financial management at the regional level still faces challenges in transparency and accountability. This study aims to analyze the factors influencing the intention to adopt Blockchain technology in public financial management within the Kutai Kartanegara Regency Government. Employing a quantitative approach with a survey method, data were gathered from 62 State Civil Apparatus (ASN) in BPKAD, Bapenda, and the Regional Inspectorate using a purposive sampling technique. Data analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that the model has strong explanatory power (R2 = 0.762) and good predictive relevance (Q2 = 0.503). Partially, Stakeholders and Competency are proven to have a significant positive influence on Blockchain adoption intention. Conversely, Relative Advantage, Complexity, Laws and Regulations, and Top Management Support show no significant effect. Theoretically, this study shows that human resource capacity and external stakeholder support are more dominant than technological characteristics at the early stage of innovation diffusion.